Molecular identification of isolates from local microorganisms as potential biofertilizer - Abdul Hasyim Sodiq; Mieke Rochimi Setiawati; Dwi Andreas Santosa; Dedi Widayat (Universitas Sebelas Maret, 2021)
Local microorganisms (MOL) are liquid fertilizers commonly used by farmers to help increase crop production. Beneficial microbes in MOL need to characterize their interactions and ability to produce growth drive compounds. The purpose of this research is to identify the superior microbial isolates from MOL made by farmers from Cibodas Lembang Bandung, Indonesia that can produce phytohormones as biofertilizers. The results of the microbial selection of MOL derived from three best microbes are 1A-2 NFB, 4A-1 NFB, and 4B-1 NFB with the ability to produce auxin, i.e., 19.41 ppm, 17.18 ppm, and 10.59 ppm, respectively. The compatibility test between the three isolates showed negative results so that it was possible to apply three microbes as a consortium. The results of a molecular identification with a 16S rRNA analysis indicate strain microbe 1A-2 NFB: Bacillus cereus (99.88% homology), 4A-1 NFB: Bacillus cereus (99.76% homology), and 4B-1 NFB: Lysinibacillus sp. (99.88% homology).